Medición del nivel de satisfacción de los clientes del banco de desarrollo S.A. agencia el Coca de la ciudad de Francisco de Orellana, provincia de Orellana para el año 2016 - Fernández Cortez, Carmen Sulay (2017)
The quality of a service is fundamental for the organizations since it determines the decisions of the clients in several areas and aspects, for this reason that each service delivered must be constantly improved. The general objective of this thesis is to measure the level of customer satisfaction of Bancodesarrollo S.A. Coca agency of the city of Francisco de Orellana for 2016, which allows a development proposal for BANCODESARROLLO. Therefore, methods and techniques were applied, within the former the inductive method, the deductive method and the statistical method were used; and, regarding the techniques, the bibliographic research was applied, the interview made to the head of the Agency and the survey made to the clients of internal and external clients; As for the sample of 362 surveys, it was obtained considering the Bank's customer population of April 2016. In addition, the employees of Bancodesarrollo, Agencia El Coca were surveyed, adding up to a total of 12 people. In the same way, it was known that Bancodevelopment, should improve in which the presentation of their products, that there is a percentage that believes that they are regular, with respect to the price of their products, that the direct sale of the company it is limited, that it does not invest in promoting its products, and that its workers are not satisfied in their entirety. Regarding the level of satisfaction of external customers, they rate the company's staff competence between good and very good, that is to say, with a satisfaction score, the time they take in the company to qualify it as good, that is, with a score. of satisfaction, the quality of the products and services that Bancodesarrollo de buenos has, with a satisfaction score, the reliability of Bancodevelopment qualify it with dissatisfaction that is to say as bad, the prices that it has qualify it with bad that is to say there is a dissatisfaction, and as regards the company itself, they qualify it as very good, that is to say, complacency. Regarding the level of satisfaction of the internal customers, they qualify Bancodesarrollo, as regards the place where they carry out their activities, they qualify it as good, that is to say with satisfaction, the internal communication qualify it as good, that is to say with satisfaction, the degree of satisfaction of working in Bancodesarrollo they qualify it as very good, that is to say, with complacency. In terms of training, they qualify it as good, that is, with satisfaction and in customer service, they qualify it as good, that is, with satisfaction. Therefore, it was necessary to propose solution strategies that will contribute to improving the satisfaction of the Agency's clients; However, to carry out these strategies, the Head of Agency and the personnel involved must understand that they need to reinvest their resources, in the implementation of quality control systems, as well as in training their workers and distributors.